Dysfunction of the noradrenergic system drives inflammation, α-synucleinopathy, and neuronal loss in mouse colon - Song, Sheng; Tu, Dezhen; Meng, Chengbo; Liu, Jie; Wilson, Belinda; Wang, Qingshan; Shih, Yen-Yu Ian; Gao, Hui-Ming; Hong, Jau-Shyong (Frontiers in Immunology, 2023)
Clinical and pathological evidence revealed that α-synuclein (α-syn) pathology seen in PD patients starts in the gut and spreads via anatomically connected structures from the gut to the brain. Our previous study demonstrated that depletion of central norepinephrine (NE) disrupted brain immune homeostasis, producing a spatiotemporal order of neurodegeneration in the mouse brain. The purpose of this study was 1) to determine the role of peripheral noradrenergic system in the maintenance of gut immune homeostasis and in the pathogenesis of PD and 2) to investigate whether NE-depletion induced PD-like α-syn pathological changes starts from the gut. For these purposes, we investigated time-dependent changes of α-synucleinopathy and neuronal loss in the gut following a single injection of DSP-4 (a selective noradrenergic neurotoxin) to A53T-SNCA (human mutant α-syn) over-expression mice. We found DPS-4 significantly reduced the tissue level of NE and increased immune activities in gut, characterized by increased number of phagocytes and proinflammatory gene expression. Furthermore, a rapid-onset of α-syn pathology was observed in enteric neurons after 2 weeks and delayed dopaminergic neurodegeneration in the substantia nigra was detected after 3-5 months, associated with the appearance of constipation and impaired motor function, respectively. The increased α-syn pathology was only observed in large, but not in the small, intestine, which is similar to what was observed in PD patients. Mechanistic studies reveal that DSP-4-elicited upregulation of NADPH oxidase (NOX2) initially occurred only in immune cells during the acute intestinal inflammation stage, and then spread to enteric neurons and mucosal epithelial cells during the chronic inflammation stage. The upregulation of neuronal NOX2 correlated well with the extent of α-syn aggregation and subsequent enteric neuronal loss, suggesting that NOX2-generated reactive oxygen species play a key role in α-synucleinopathy. Moreover, inhibiting NOX2 by diphenyleneiodonium or restoring NE function by salmeterol (a β2-receptor agonist) significantly attenuated colon inflammation, α-syn aggregation/propagation, and enteric neurodegeneration in the colon and ameliorated subsequent behavioral deficits. Taken together, our model of PD shows a progressive pattern of pathological changes from the gut to the brain and suggests a potential role of the noradrenergic dysfunction in the pathogenesis of PD.